Low-Grade Appendiceal Mucinous Neoplasm in an Adolescent Patient With Untreated Crohn's Disease. Issue 3 (16th March 2020) - Hernández Benabe, Stefany; Leeman, Rachel; Brady, Ann C.; Hirzel, Alicia; Langshaw, Amber H.
ABSTRACT: Appendiceal mucinous neoplasms are rarely diagnosed in pediatric patients. We present a 16-year-old adolescent boy with severe Crohn's disease who was not on maintenance medication for his underlying diagnosis. He was referred for nutritional optimization and small bowel obstruction. An emergent laparoscopic ileocecectomy with primary ileocolonic anastomosis was carried out secondary to acute peritonitis. Small bowel pathologic findings were consistent with Crohn's disease with low-grade appendiceal mucinous neoplasm (LAMN) of the appendix.